1983
DOI: 10.1007/bf01258156
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence that Retzius-Cajal cells transform to nonpyramidal neurons in the developing rat visual cortex

Abstract: Electron microscopy and tritiated thymidine autoradiographic techniques were used to study the life history of Retzius-Cajal cells in the developing visual cortex of the rat, a subject which has long been debated by investigators. The findings show unequivocally that at least some of these characteristic cells of the immature animals remain in the adult cortex in the form of typical nonpyramidal neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 14 publications
2
49
0
Order By: Relevance
“…It has been proposed that Cajal-Retzius cells undergo a progressive degeneration during cortical development in rodents (Derer and Derer, 1990;Ferrer et al, 1990;Del Rio et al, 1995;see also Supér et al, 1998 for review), and regressive changes have been observed with different techniques in the Cajal-Retzius cells of the human cortex at different developmental ages (Meyer and Gonzalez-Hernandez, 1993;Uylings and Delalle, 1997;Meyer and Goffinet, 1998). It has also been reported that the Cajal-Retzius cells are transformed during corticogenesis from a fetal to an adult persistent form of nonpyramidal neurons (Edmunds and Parnavelas, 1982;Parnavelas and Edmunds, 1983). However, other data argue against the death or transformation of Cajal-Retzius cells, indicating that their disappearance should be ascribed to a progressive dispersion due to cortical growth (Marin-Padilla, 1984, 1998Mrzljak et al, 1990).…”
Section: Cell Death Versus Cell Migration In the Development Of Humanmentioning
confidence: 89%
“…It has been proposed that Cajal-Retzius cells undergo a progressive degeneration during cortical development in rodents (Derer and Derer, 1990;Ferrer et al, 1990;Del Rio et al, 1995;see also Supér et al, 1998 for review), and regressive changes have been observed with different techniques in the Cajal-Retzius cells of the human cortex at different developmental ages (Meyer and Gonzalez-Hernandez, 1993;Uylings and Delalle, 1997;Meyer and Goffinet, 1998). It has also been reported that the Cajal-Retzius cells are transformed during corticogenesis from a fetal to an adult persistent form of nonpyramidal neurons (Edmunds and Parnavelas, 1982;Parnavelas and Edmunds, 1983). However, other data argue against the death or transformation of Cajal-Retzius cells, indicating that their disappearance should be ascribed to a progressive dispersion due to cortical growth (Marin-Padilla, 1984, 1998Mrzljak et al, 1990).…”
Section: Cell Death Versus Cell Migration In the Development Of Humanmentioning
confidence: 89%
“…The answer to the first question is not straightforward. While some cells die [Kostovic and Rakic, 1980;Luskin and Shatz, 1985], some change their morphology or transform into other cells that migrate to the lower strata [Parnavelas and Edmunds, 1983], and others become diluted in this tissue as a consequence of the growth of the cerebral cortex [König et al, 1977;Marín-Padilla, 1998]. Our studies of apoptosis in developing rodents showed that some cell death does occur in the cortex at P1, and the number of cells that die increases during the 1st postnatal week, reaching a peak around P6-P8 and after which it declines [Valverde et al, 1995b].…”
Section: Neuronal Expression Within the Pp And Mzmentioning
confidence: 99%
“…While some of these cells will die or transform into other nonpyramidal neurons [Derer and Derer, 1990;Del Rio et al, 1995;Parnavelas and Edmunds, 1983], the remainder will form the layer 1 of the cortex. The cells that are generated at E12 accumulated below the pial membrane and began to form the PP, despite the fact that some of these cells are able to migrate tangentially along this stratum towards the basal telencephalon [Tomioka et al, 2000;Jiménez et al, 2002].…”
Section: Generation Of Layer 1 Cellsmentioning
confidence: 99%
“…A common assumption is that only a subset of the C-R cells survives into adulthood (Sidman and Rakic, 1982;Marin-Padilla, 1998;Meyer and Goffinet, 1998) and that many of them change their morphology (Poliakov, 1961;Konig and Marty, 1981;Parnavelas and Edmunds, 1983). The dilution, caused by the growth of the neocortex, may also play a role in the diminishing density of C-R cells in layer I, particularly in humans, in which the thickness of layer I quadruples and the surface expands 200-fold during postnatal development (Blinkov and Glezer, 1968).…”
Section: Function and Fatementioning
confidence: 99%